Exploring the Transfer of Cultural Specificity in Film Subtitling : The Case Study of University Teachers of European Universities - BENLAHRACHE, Wafa Safinez (Journal of Human Sciences, 2017)
The basic aim of the present paper is to explore the way cultural specificity is rendered in film subtitling and how it is approached at the academic level. To this end, a questionnaire was administered online to ten teachers of subtitling from different European universities in order to gather direct information about the general issues surrounding this topic and attain a deeper perception of the methodologies followed by professionals in the field together with their ensuing problems and limitations.